PROTEOMIK: DATABASE DAN TEKNOLOGI - Azmi Azhari (Universitas Lambung Mangkurat, 2017)
Abstract. Today the field of proteomics become one of the scientific disciplines that the spotlight of science. The integration of proteomics and bioinformatics studies linking between the database and technology. Databases are very helpful in the field of proteomics research. Database integrated into the proteomics experiment, aimed at determining the identity, characteristics, and interactions of proteins. An application form The GDPE is a web-based application with a relational database based PRIDE XML format. Protein sequence database provides peptide sequences that will be matched with tandem mass spectrum by search engines. Proteomic study the use of advanced tools called MALDI stands for Matrix-Assisted Laser Desorption/Ionization, with this tool will be known about the structure and function of a protein. The technique used in the study of proteomics analysis of which is in the form of 2D electrophoresis gel so as to separate, identify and measure the molecular weight. Another technology is highly sensitive mass spectrometry, and High-Performance Liquid Chromatography (HPLC).Keywords: proteomics, database, proteomics technology